Purine metabolites in the activity of purine nucleoside phosphorylase (Revista Española de Fisiología, 1976)
In the phosphorolytic degradation catalyzed by chicken liver PNPase (E.C. 2.4.2.1) inosine appears to behave as a better substrate than xanthosine. Hypoxanthine, xanthine, guanine and purine (1 X 10(-1)M) appear to be inhibitors of the pigeon liver PNPase, whereas allopurinol, ATP, ITP, CTP and UTP (1. X 10(-3) M) do not inhibit the enzyme. Both PNPase activities exhibit the same optimum temperature (37-40 degrees C). Chicken liver PNPase optimum pH is in the range 6.5-7, whereas that of pigeon liver is in the range 7-7.5. Lineweaver-Burk plots for the inosine phosphorolysis catalyzed by chicken liver PNPase yielded straight lines if substrate concentrations were lower than 1 X 10(-4) M but concave downward curves at higher concentrations. This activation increases when the homogenates are stored at 4 degrees C and pH = 7 during 24 h or more; pigeon liver PNPase does not show this activation phenomenon.